1986
DOI: 10.1017/s0033822200007529
|View full text |Cite
|
Sign up to set email alerts
|

14C Dating of Plant Macrofossils in Lake Sediment

Abstract: ABSTRACT. Macrofossils of terrestrial plants have been picked from a sediment core taken in Lake Lobsigen, a small lake on the Western Swiss Plateau. The sediments were previously analyzed for pollen composition, plant and animal macrofossils, and stable isotopes. Plant macrofossils were selected near pollen zone boundaries in Late Glacial and early Postglacial sediment for 14C dating by AMS. In the same lake carbonate and gyttja (aquatic plant) samples were dated by decay counting. The dates on terrestrial ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(44 citation statements)
references
References 6 publications
(5 reference statements)
3
38
0
2
Order By: Relevance
“…Bulk organic samples from the bottoms of lake cores avoid problems associated with marine samples such as marine reservoir variations (Mangerud, 1972;Hjort, 1973;Mangerud and Gullikson, 1975;Bard, 1988;Bard et al, 1994;Birks et al, 1996) and the influences of meltwater in the marine environment (Sutherland, 1986;Hillaire-Marcel, 1988;Rodrigues, 1992). However, lacustrine bulk sediment samples can also yield anomalous old ages for other reasons (Shotton, 1972;Oeschger et al, 1985;Andrée et al, 1986;Wohlfarth, 1996). Aquatic plants as well as other aquatic organisms, which are frequently a significant part of bulk organic samples from lake cores, acquire carbon from lake water in which the concentration of 14 C may be lower than the atmosphere.…”
Section: Discussion: An Accurate Terrestrial 14 C Chronologymentioning
confidence: 99%
See 2 more Smart Citations
“…Bulk organic samples from the bottoms of lake cores avoid problems associated with marine samples such as marine reservoir variations (Mangerud, 1972;Hjort, 1973;Mangerud and Gullikson, 1975;Bard, 1988;Bard et al, 1994;Birks et al, 1996) and the influences of meltwater in the marine environment (Sutherland, 1986;Hillaire-Marcel, 1988;Rodrigues, 1992). However, lacustrine bulk sediment samples can also yield anomalous old ages for other reasons (Shotton, 1972;Oeschger et al, 1985;Andrée et al, 1986;Wohlfarth, 1996). Aquatic plants as well as other aquatic organisms, which are frequently a significant part of bulk organic samples from lake cores, acquire carbon from lake water in which the concentration of 14 C may be lower than the atmosphere.…”
Section: Discussion: An Accurate Terrestrial 14 C Chronologymentioning
confidence: 99%
“…However, comparing bulk 14 C ages with an existing lake bottom chronology that is also based on bulk sediment ages does not allow us to recognize more subtle errors (<1000 yr) that may be pervasive. This can only be accomplished with a direct comparison of bulk sediment and plant macrofossil ages, which have systematically been different by 300-800 yr in European lake sediment studies (Oeschger et al, 1985;Andrée et al, 1986;Wohlfarth, 1996). Although it is possible for a bulk sediment sample to yield an accurate atmospheric 14 C age, systematic testing for subtle errors has not been incorporated into any chronology in New England.…”
Section: Discussion: An Accurate Terrestrial 14 C Chronologymentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to problems such as dissolved carbonates in water or detrital carbon reworked from carbon-bearing rocks and sediments. In Switzerland, for example, Andree et al (1986) found an 800-year offset in radiocarbon age between bulk sediment and AMS plant macrofossil ages for the late-glacial interval, while offsets of up to 8 ka occur in basal lake sediments in central North America (Grimm et al, 2009). In another example, the initiation of 13 lakes/bogs across a landscape previously covered by the south-eastern LIS provided a tight cluster of AMS ages between 16 and 15 ka (Peteet et al, 2012), which is 5-9 ka later than the time of ice retreat based upon the extrapolation of bulk chronologies (Dyke et al, 2003), varves (Ridge, 2004), and cosmogenic dates (Balco et al, 2009).…”
Section: Radiocarbon Dating and Pan-ice Sheet Margin Chronologiesmentioning
confidence: 99%
“…Although the hardwater effect is relatively well understood (e.g., Andrée et al, 1986 , 1991;Barnerkow et al, 1998;Grimm et al, 2009), the processes involving transport and incorporation of soil organic matter in aquatic systems, and the effect of soil organic carbon on bulk radiocarbon ages in general, remains poorly constrained (e.g., Eglinton, 2010). The few authors that address the issue conclude that bulk radiocarbon ages are not accurate enough to provide reliable core chronologies (Björck and Håkansson, 1982;Björck et al, 1998;Abbott and Stafford, 1996) but they do not propose a method to correct ages obtained on such samples, although Björck and Håkansson (1982) noticed that the age difference is related to the amount of re-deposited pollen grains and inversely related to the total organic carbon content (TOC) of the sediment.…”
Section: Introductionmentioning
confidence: 99%